Fuzzy-sets decision-support system for geotechnical site soundings - Boumezerane, Djemalddine M. (Acta geotechnica Slovenica, 2011)
A geotechnical site investigation is an important and complex task that is generally carried out in two steps. The first step, consisting of preliminary soundings, guides the subsequent site characterization. The number of soundings required to adequately characterize a site is set on the basis of an engineering judgement following the preliminary investigation, this is affected by the geological context, the area topography, the project type, and the knowledge of the neighbouring areas. A fuzzy-sets decision-support system, considering parameters that affect the number of soundings required to adequately characterize a site, is proposed. Parameter uncertainties and a lack of information are also considered. On the basis of the available qualitative and quantitative information, the proposed fuzzy system makes it possible to estimate, for a common project, the number of site soundings required to adequately characterize the site. The cases presented show that a Fuzzy Inference System can be used as a systematic decision-support tool for engineers dealing with site characterizations.
Keywords: fuzzy inference; fuzzy sets; geotechnical investigation; geotehnično raziskovanje; mehke množice; mehko sklepanje; negotovosti; soundings number; število sond; uncertainties